Prevalence of HPV-16 genomic variant carrying a 63-bp duplicated sequence within the E1 gene in Slovenian women - Bogovac, Željka (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2011)
High-risk HPV, particularly HPV-16, is etiologically associated with the development of cervical cancer and its precursor lesions - cervical intraepithelial neoplasia (CIN). However, most precancerous lesions will not progress to cancer. Numerous studies have shown that HPV-16 consists of several genomic variants, which differ in their association with cervical cancer, viral persistence and the frequency of recurrence of cervical disease.Recently, a novel, presumably less pathogenic, HPV-16 E6-T350G genomicvariant has been identified, carrying a 63-bp in-frame insertion in theE1 gene. No data from Slovenian patients have so far been reported for thisspecific HPV-16 variant. In the present study, therefore, a total of 390 HPV-16 positive samples obtained from the same number of women with normal cytology, CIN I, CIN II, CIN III or cervical cancer, were analyzed. The HPV-16E1 insert variant was detected using real-time PCR-amplification of a 146-210-bp fragment of the E1 gene and PCR-sequencing of a 169-bp fragment of the E6 gene. The HPV-16 E1 insert variant was identified in 7/48 (14.6%), 1/21(4.8%), 2/20 (10.0%), 9/131 (6.9%) and 12/170 (7.1%) of women with normal cytology, CIN I, CIN II, CIN III and cervical cancer, respectively. All HPV-16E1 insert variants with an amplifiable E6 gene belonged to the European HPV-16 E6-350G variant group. No statistically significant differences in the prevalence of HPV-16 E1 insert genomic variant in women presenting with normalcytology and those with the different stages of HPV-16-induced disease were found.
Keywords: Cervical Intraepithelial Neoplasia; Cervix Neoplasms; Genetics; genetika; Genom virusni; Genome, Viral; ginekologija; infekcije; Maternica, vrat, intraepitelijska neoplazija; maternični vrat; Maternični vrat, novotvorbe; Papilloma; Papillomavirus, Human; Papilom; papiloma virusi; Papilomavirus človeški; Polimerazna, verižna reakcija; Polymerase Chain Reaction